Isochlorogenic Acid A Attenuates the Progression of Liver Fibrosis Through Regulating HMGB1/TLR4/NF-κB Signaling Pathway - Liu, Xin; Huang, Kai; Zhang, Ru Jiao; Mei, Dan; Zhang, Bo (Frontiers in Pharmacology, 2020)
Liver fibrosis, a chronic damage process related to further progression of hepatic cirrhosis, has yet no truly effective treatment. Isochlorogenic acid A (ICQA), isolated from a traditional Chinese herbal medicine named Laggeraalata (Asteraceae), is proved to exhibit anti-inflammatory, hepatoprotective and antiviral properties. However, the effects of ICQA on liver fibrosis are poorly understood. This study aimed to investigate the effects of ICQA on liver fibrosis and clarify the underlying mechanism. Liver fibrosis was induced in an animal model by treating rats with carbon tetrachloride (CCl4) for eight weeks, and ICQA was orally administered every day at three doses (10, 20 and 40 mg/kg). Our results showed that ICQA had significant protective effects on liver injury, inflammation and fibrosis in vivo. Meanwhile, ICQA prevented the activation of hepatic stellate cells (HSC), indicated by its inhibitory effect on the overexpression of α-smooth muscle actin (α-SMA). The reduced fibrosis was found to be associated with the decreased protein expression of high-mobility group box 1 (HMGB1) and toll like receptor (TLR)4. Simultaneously, ICQA can also suppress the cytoplasmic translocation of HMGB1 in rat liver. Further investigations indicated that ICQA treatment dramatically attenuated nuclear translocation of the nuclear factor-kB (NF-κB) p65 and inhibited the hepatic expression of p‑IκBα in rats with liver fibrosis. Taken together, our results indicate that ICQA has hepatoprotective and anti-fibrotic effects in vivo, and the mechanism of which may be involved in modulating the HMGB1/TLR4/NF-κB signaling pathways.